High-strength alloy for antenna and preparation process of high-strength alloy
By plating copper plating layers on the surface of antenna materials and adding carbon nanotubes-silicon dioxide complexes, the existing antenna material has a more efficient and reliable signal transmission in terms of strength and corrosion resistance.
Patent Information
- Application Number
- CN202411443106.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-16
AI Technical Summary
Existing antenna materials have limitations in strength, corrosion resistance and stability, and it is difficult to meet the strength and reliability needs of modern antennas.
The aluminum alloy is used as the basic material, and the surface is plated on its surface through electroplating technology. At the same time, the carbon nano-nanotuba-silicon dioxide complex is added to the electroplating solution to enhance the strength and conductivity of the alloy.
Improve the strength, conductivity and corrosion resistance of the antenna alloy, and enhance the efficiency and reliability in signal transmission.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of alloys, in particular to a high-strength alloy for antennas and a preparation process thereof. Background Art
[0002] With the promotion of 5G communication technology, the performance requirements for antenna materials are becoming increasingly stringent. The performance of the antenna can directly affect the transmission quality and coverage of the signal. Alloys are an important component of antennas due to their excellent mechanical properties and good electromagnetic properties.
[0003] Traditional antenna materials are mostly metals such as aluminum and copper, which have certain limitations in strength, corrosion resistance and stability. As antenna design develops towards miniaturization and lightweight, ordinary metal materials are difficult to meet the strength and reliability requirements of modern antennas. Therefore, it is particularly important to develop a high-strength alloy material that can optimize electrical conductivity and corrosion resistance while ensuring mechanical strength.
[0004] In order to solve the above problems and improve the strength, the present invention provides a high-strength alloy for antenna and a preparation process thereof. Summary of the invention
[0005] The object of the present invention is to provide a high-strength alloy for antenna and a preparation process thereof, so as to solve the problems raised in the prior art.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A preparation process of a high-strength alloy for antennas comprises the following steps:
[0008] Step 1: Take Mg, Si, Fe, Cu, Cr, Mn, Ti, Zn, and Al, melt at 745-760°C, refine at 740-745°C for 40-60min, stand for 30-40min, cast, heat treat, and then perform rough rolling, cold rolling, cleaning, annealing, cooling, and grinding to obtain aluminum alloy;
[0009] Step 2: Take the aluminum alloy, pickle it, wash it with water, dry it, and then place it in an electroplating solution for electroplating to obtain a high-strength alloy for antennas;
[0010] The electroplating solution comprises: 300-350 mL / L of copper sulfate, 85-100 mL / L of an accelerator, 2-4 mL / L of polyethylene glycol, 0.1-0.3 g / L of a carbon nanotube-silicon dioxide compound, and the rest is deionized water.
[0011] More optimally, the aluminum alloy includes the following components, in weight percentage: 1wt%-1.5wt% Mg, 0.6wt%-0.9wt% Si, 0.1wt%-0.4wt% Fe, 0.1wt%-0.15wt% Cu, 0.07wt%-0.1wt% Cr, 0.05wt%-0.15wt% Mn, 0.04wt%-0.085wt% Ti, 0.03wt%-0.08wt% Zn, and the balance is Al.
[0012] Preferably, the method for preparing the carbon nanotube-silicon dioxide composite comprises the following steps:
[0013] S1: Take deionized water, add tris(hydroxymethylaminomethane) hydrochloric acid solution, adjust the pH value to 8.3-8.5, add copper-plated carbon nanotubes and dopamine hydrochloride powder, stir for 5-6 hours, centrifuge and dry to obtain copper-plated carbon nanotubes coated with polydopamine;
[0014] S2: Take deionized water and anhydrous ethanol, stir evenly, add copper-plated carbon nanotubes coated with polydopamine and modified silica, heat to 65-70°C, ultrasonically disperse for 30-40 minutes, then stir for 5-6 hours, filter and dry to obtain a carbon nanotube-silica composite.
[0015] More optimally, the preparation method of the copper-plated carbon nanotubes is: take carbon nanotubes and deionized water, ultrasonically disperse them to obtain a carbon nanotube suspension, add the carbon nanotubes to plating solution A, heat it to 65-70°C, add formaldehyde, and electroplate for 110-120 minutes to obtain copper-plated carbon nanotubes.
[0016] More optimally, the preparation method of the plating solution A is: using deionized water as a solvent, taking copper sulfate pentahydrate, potassium sodium tartrate, and ethylenediaminetetraacetic acid, stirring evenly, adding polyethylene glycol, and then dropping sodium hydroxide solution, adjusting the pH value to 11-12, to obtain plating solution A.
[0017] More optimally, the preparation method of the modified silica is: take amino silica and deionized water, stir evenly, ultrasonically disperse for 20-30 minutes, heat to 55-60°C, add 1H,1H,2H,2H-perfluorooctyltriethoxysilane and acetic acid, heat to 75-80°C, stir for 6-7 hours, filter and dry to obtain modified silica.
[0018] More optimally, the preparation method of the amino silica is: take silica and anhydrous toluene, stir evenly, ultrasonically disperse for 20-30 minutes, add aminopropyltriethoxysilane, heat to boiling after nitrogen filling, reflux at a constant temperature of 105°C for 46-50 hours, wash and dry to obtain amino silica.
[0019] More optimally, the promoter is any one or more of sodium citrate and potassium tartrate.
[0020] More optimally, in step 2, during the electroplating process, the plating solution temperature is 55-65°C and the electroplating time is 12-15 minutes.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] 1. The present invention uses aluminum alloy as the antenna. Aluminum alloy is light in weight and has good conductivity. In order to further improve the conductivity of the antenna and make the antenna more efficient in signal transmission, the present invention adopts electroplating technology to plate a copper layer on the surface of the aluminum alloy.
[0023] 2. Adding carbon nanotube-silicon dioxide complex to the electroplating solution enhances the strength of the alloy for antennas. Carbon nanotubes are strong, and copper plating on the surface of carbon nanotubes improves the conductivity of the antenna. At the same time, copper plating on the surface of carbon nanotubes can improve the bonding force between carbon nanotubes and copper plating, and improve the adhesion of the electroplating layer, thereby enhancing the durability and reliability of the alloy for antennas.
[0024] 3. 1H,1H,2H,2H-perfluorooctyl triethoxysilane was used to modify silicon dioxide to enhance the corrosion resistance of the alloy for antenna. Carbon nanotubes were compounded with modified silicon dioxide to improve the agglomeration of carbon nanotubes. The silicon dioxide was first subjected to amino treatment. The amino group can enhance the interaction between amino silicon dioxide and carbon nanotubes, improve the interface compatibility between the two, and further strengthen the strength of the alloy for antenna. DETAILED DESCRIPTION
[0025] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] The sources and types of the substances involved in the present invention are not particularly limited, and exemplary examples include: silicon dioxide: particle size 80-120 nm; carbon nanotubes: diameter: 10-20 nm; length: 10-30 um.
[0027] Embodiment 1: A process for preparing a high-strength alloy for antennas, comprising the following steps:
[0028] Step 1: Preparation of aluminum alloy:
[0029] Mg, Si, Fe, Cu, Cr, Mn, Ti, Zn and Al are melted at 750°C, refined at 742°C for 50 min, left to stand for 35 min, cast, heat treated, then rough rolled, cold rolled, cleaned, annealed, cooled and polished to obtain an aluminum alloy;
[0030] The aluminum alloy includes the following components, in terms of weight percentage: 1.2wt% Mg, 0.8wt% Si, 0.3wt% Fe, 0.12wt% Cu, 0.08wt% Cr, 0.1wt% Mn, 0.05wt% Ti, 0.04wt% Zn, and the balance is Al;
[0031] Step 2: Take the aluminum alloy, pickle, wash with water, dry, and then place it in an electroplating solution for electroplating. The plating solution temperature is 60° C. and the electroplating time is 13 minutes; a high-strength alloy for antenna is obtained;
[0032] The composition of the electroplating solution is: 320 mL / L of copper sulfate, 90 mL / L of accelerator sodium citrate, 3 mL / L of polyethylene glycol, 0.2 g / L of carbon nanotube-silicon dioxide composite, and the rest is deionized water;
[0033] Step 3: Preparation of copper-plated carbon nanotubes:
[0034] Using deionized water as solvent, take 15 g / L of copper sulfate pentahydrate, 10.5 g of potassium sodium tartrate, and 20 g / L of ethylenediaminetetraacetic acid, stir evenly, add 2 mL / L of polyethylene glycol, then dropwise add sodium hydroxide solution, adjust the pH value to 11.5, and obtain plating solution A;
[0035] Take 0.1g carbon nanotubes and 50mL deionized water, and ultrasonically disperse them to obtain a carbon nanotube suspension. Add the carbon nanotubes to plating solution A, heat it to 68°C, add 4.5g / L formaldehyde, and electroplate for 115min to obtain copper-plated carbon nanotubes.
[0036] Step 4: Preparation of amino silicon dioxide:
[0037] Take 5g of silica and 300mL of anhydrous toluene, stir evenly, ultrasonically disperse for 25min, add 20g of aminopropyltriethoxysilane, heat to boiling after nitrogen filling, reflux at a constant temperature of 105°C for 47h, wash and dry to obtain amino silica;
[0038] Step 5: Preparation of modified silica:
[0039] Take 6 g of amino silica and 300 mL of deionized water, stir evenly, disperse by ultrasonication for 25 min, heat to 57 ° C, add 1 g of 1H, 1H, 2H, 2H-perfluorooctyl triethoxysilane and 0.5 g of acetic acid, heat to 78 ° C, stir for 6.5 h, filter and dry to obtain modified silica;
[0040] Step 6: Preparation of carbon nanotube-silicon dioxide composite:
[0041] S1: Take 1000 mL of deionized water, add tris(hydroxymethylaminomethane) hydrochloric acid solution, adjust the pH value to 8.4, add 0.1 g of copper-plated carbon nanotubes and 3 g of dopamine hydrochloride powder, stir for 5 h, centrifuge and dry to obtain copper-plated carbon nanotubes coated with polydopamine;
[0042] S2: Take 100 mL of deionized water and 50 mL of anhydrous ethanol, stir evenly, add 1 g of copper-plated carbon nanotubes coated with polydopamine and 2 g of modified silica, heat to 68°C, ultrasonically disperse for 35 minutes, then stir for 5.5 hours, filter and dry to obtain a carbon nanotube-silica composite.
[0043] Embodiment 2: A process for preparing a high-strength alloy for antenna, comprising the following steps:
[0044] Step 1: Preparation of aluminum alloy:
[0045] Mg, Si, Fe, Cu, Cr, Mn, Ti, Zn and Al are melted at 745°C, refined at 740°C for 40 min, left to stand for 30 min, cast, heat treated, then rough rolled, cold rolled, cleaned, annealed, cooled and polished to obtain an aluminum alloy;
[0046] The aluminum alloy includes the following components, calculated by weight percentage: 1wt% Mg, 0.6wt% Si, 0.1wt% Fe, 0.1wt% Cu, 0.07wt% Cr, 0.05wt% Mn, 0.04wt% Ti, 0.03wt% Zn, and the balance is Al;
[0047] Step 2: Take the aluminum alloy, pickle, wash with water, dry, and then place it in an electroplating solution for electroplating. The plating solution temperature is 55° C. and the electroplating time is 12 minutes; a high-strength alloy for antenna is obtained;
[0048] The composition of the electroplating solution is: 300 mL / L of copper sulfate, 85 mL / L of accelerator sodium citrate, 2 mL / L of polyethylene glycol, 0.1 g / L of carbon nanotube-silicon dioxide composite, and the rest is deionized water;
[0049] Step 3: Preparation of copper-plated carbon nanotubes:
[0050] Using deionized water as solvent, take 15 g / L of copper sulfate pentahydrate, 10.5 g of potassium sodium tartrate, and 20 g / L of ethylenediaminetetraacetic acid, stir evenly, add 2 mL / L of polyethylene glycol, then dropwise add sodium hydroxide solution, adjust the pH value to 11, and obtain plating solution A;
[0051] Take 0.1g carbon nanotubes and 50mL deionized water, and ultrasonically disperse them to obtain a carbon nanotube suspension. Add the carbon nanotubes to plating solution A, heat it to 65°C, add 4.5g / L formaldehyde, and electroplate for 110min to obtain copper-plated carbon nanotubes.
[0052] Step 4: Preparation of amino silicon dioxide:
[0053] Take 5g of silica and 300mL of anhydrous toluene, stir evenly, ultrasonically disperse for 20min, add 20g of aminopropyltriethoxysilane, heat to boiling after nitrogen filling, reflux at a constant temperature of 105°C for 46h, wash and dry to obtain amino silica;
[0054] Step 5: Preparation of modified silica:
[0055] Take 6 g of amino silica and 300 mL of deionized water, stir evenly, disperse by ultrasonication for 20 min, heat to 55 ° C, add 1 g of 1H, 1H, 2H, 2H-perfluorooctyl triethoxysilane and 0.5 g of acetic acid, heat to 75 ° C, stir for 6 h, filter and dry to obtain modified silica;
[0056] Step 6: Preparation of carbon nanotube-silicon dioxide composite:
[0057] S1: Take 1000 mL of deionized water, add tris(hydroxymethylaminomethane) hydrochloric acid solution, adjust the pH value to 8.3, add 0.1 g of copper-plated carbon nanotubes and 3 g of dopamine hydrochloride powder, stir for 5 h, centrifuge and dry to obtain copper-plated carbon nanotubes coated with polydopamine;
[0058] S2: Take 100 mL of deionized water and 50 mL of anhydrous ethanol, stir evenly, add 1 g of copper-plated carbon nanotubes coated with polydopamine and 2 g of modified silica, heat to 65°C, ultrasonically disperse for 30 minutes, then stir for 5 hours, filter and dry to obtain a carbon nanotube-silica composite.
[0059] Embodiment 3: A process for preparing a high-strength alloy for antenna, comprising the following steps:
[0060] Step 1: Preparation of aluminum alloy:
[0061] Mg, Si, Fe, Cu, Cr, Mn, Ti, Zn and Al are melted at 760°C, refined at 745°C for 60 min, left to stand for 40 min, cast, heat treated, then rough rolled, cold rolled, cleaned, annealed, cooled and polished to obtain an aluminum alloy;
[0062] The aluminum alloy includes the following components, in terms of weight percentage: 1.5wt% Mg, 0.9wt% Si, 0.4wt% Fe, 0.15wt% Cu, 0.1wt% Cr, 0.15wt% Mn, 0.085wt% Ti, 0.08wt% Zn, and the balance is Al;
[0063] Step 2: Take the aluminum alloy, pickle, wash with water, dry, and then place it in an electroplating solution for electroplating. The plating solution temperature is 65° C. and the electroplating time is 15 minutes; a high-strength alloy for antenna is obtained;
[0064] The composition of the electroplating solution is: 350 mL / L of copper sulfate, 100 mL / L of accelerator sodium citrate, 4 mL / L of polyethylene glycol, 0.3 g / L of carbon nanotube-silicon dioxide composite, and the rest is deionized water;
[0065] Step 3: Preparation of copper-plated carbon nanotubes:
[0066] Using deionized water as solvent, take 15 g / L of copper sulfate pentahydrate, 10.5 g of potassium sodium tartrate, and 20 g / L of ethylenediaminetetraacetic acid, stir evenly, add 2 mL / L of polyethylene glycol, then dropwise add sodium hydroxide solution, adjust the pH value to 12, and obtain plating solution A;
[0067] Take 0.1g carbon nanotubes and 50mL deionized water, and ultrasonically disperse them to obtain a carbon nanotube suspension. Add the carbon nanotubes to plating solution A, heat it to 70°C, add 4.5g / L formaldehyde, and electroplate for 120min to obtain copper-plated carbon nanotubes.
[0068] Step 4: Preparation of amino silicon dioxide:
[0069] Take 5g of silica and 300mL of anhydrous toluene, stir evenly, ultrasonically disperse for 30min, add 20g of aminopropyltriethoxysilane, heat to boiling after nitrogen filling, reflux at a constant temperature of 105°C for 50h, wash and dry to obtain amino silica;
[0070] Step 5: Preparation of modified silica:
[0071] Take 6 g of amino silica and 300 mL of deionized water, stir evenly, disperse by ultrasonic for 30 min, heat to 60 ° C, add 1 g of 1H, 1H, 2H, 2H-perfluorooctyl triethoxysilane and 0.5 g of acetic acid, heat to 80 ° C, stir for 7 h, filter and dry to obtain modified silica;
[0072] Step 6: Preparation of carbon nanotube-silicon dioxide composite:
[0073] S1: Take 1000 mL of deionized water, add tris(hydroxymethylaminomethane) hydrochloric acid solution, adjust the pH value to 8.5, add 0.1 g of copper-plated carbon nanotubes and 3 g of dopamine hydrochloride powder, stir for 5 h, centrifuge and dry to obtain copper-plated carbon nanotubes coated with polydopamine;
[0074] S2: Take 100 mL of deionized water and 50 mL of anhydrous ethanol, stir evenly, add 1 g of copper-plated carbon nanotubes coated with polydopamine and 2 g of modified silica, heat to 70°C, ultrasonically disperse for 40 minutes, then stir for 6 hours, filter and dry to obtain a carbon nanotube-silica composite.
[0075] Comparative Example 1: No copper is plated on the surface of the carbon nanotubes, and the rest is the same as Example 1:
[0076] A preparation process of a high-strength alloy for antennas comprises the following steps:
[0077] Step 1: Preparation of aluminum alloy:
[0078] Mg, Si, Fe, Cu, Cr, Mn, Ti, Zn and Al are melted at 750°C, refined at 742°C for 50 min, left to stand for 35 min, cast, heat treated, then rough rolled, cold rolled, cleaned, annealed, cooled and polished to obtain an aluminum alloy;
[0079] The aluminum alloy includes the following components, in terms of weight percentage: 1.2wt% Mg, 0.8wt% Si, 0.3wt% Fe, 0.12wt% Cu, 0.08wt% Cr, 0.1wt% Mn, 0.05wt% Ti, 0.04wt% Zn, and the balance is Al;
[0080] Step 2: Take the aluminum alloy, pickle, wash with water, dry, and then place it in an electroplating solution for electroplating. The plating solution temperature is 60° C. and the electroplating time is 13 minutes; a high-strength alloy for antenna is obtained;
[0081] The composition of the electroplating solution is: 320 mL / L of copper sulfate, 90 mL / L of accelerator sodium citrate, 3 mL / L of polyethylene glycol, 0.2 g / L of carbon nanotube-silicon dioxide composite, and the rest is deionized water;
[0082] Step 3: Preparation of amino silicon dioxide:
[0083] Take 5g of silica and 300mL of anhydrous toluene, stir evenly, ultrasonically disperse for 25min, add 20g of aminopropyltriethoxysilane, heat to boiling after nitrogen filling, reflux at a constant temperature of 105°C for 47h, wash and dry to obtain amino silica;
[0084] Step 4: Preparation of modified silica:
[0085] Take 6 g of amino silica and 300 mL of deionized water, stir evenly, disperse by ultrasonication for 25 min, heat to 57 ° C, add 1 g of 1H, 1H, 2H, 2H-perfluorooctyl triethoxysilane and 0.5 g of acetic acid, heat to 78 ° C, stir for 6.5 h, filter and dry to obtain modified silica;
[0086] Step 5: Preparation of carbon nanotube-silicon dioxide composite:
[0087] S1: Take 1000 mL of deionized water, add tris(hydroxymethyl)aminomethane hydrochloric acid solution, adjust the pH value to 8.4, add 0.1 g of carbon nanotubes and 3 g of dopamine hydrochloride powder, stir for 5 h, centrifuge and dry to obtain carbon nanotubes coated with polydopamine;
[0088] S2: Take 100 mL of deionized water and 50 mL of anhydrous ethanol, stir evenly, add 1 g of carbon nanotubes coated with polydopamine and 2 g of modified silica, heat to 68°C, ultrasonically disperse for 35 minutes, then stir for 5.5 hours, filter and dry to obtain a carbon nanotube-silica composite.
[0089] Comparative Example 2: The copper-plated carbon nanotubes are not compounded with modified silicon dioxide, and the rest is the same as Example 1:
[0090] A preparation process of a high-strength alloy for antennas comprises the following steps:
[0091] Step 1: Preparation of aluminum alloy:
[0092] Mg, Si, Fe, Cu, Cr, Mn, Ti, Zn and Al are melted at 750°C, refined at 742°C for 50 min, left to stand for 35 min, cast, heat treated, then rough rolled, cold rolled, cleaned, annealed, cooled and polished to obtain an aluminum alloy;
[0093] The aluminum alloy includes the following components, in terms of weight percentage: 1.2wt% Mg, 0.8wt% Si, 0.3wt% Fe, 0.12wt% Cu, 0.08wt% Cr, 0.1wt% Mn, 0.05wt% Ti, 0.04wt% Zn, and the balance is Al;
[0094] Step 2: Take the aluminum alloy, pickle, wash with water, dry, and then place it in an electroplating solution for electroplating. The plating solution temperature is 60° C. and the electroplating time is 13 minutes; a high-strength alloy for antenna is obtained;
[0095] The composition of the electroplating solution is: 320mL / L of copper sulfate, 90mL / L of accelerator sodium citrate, 3mL / L of polyethylene glycol, 0.07g / L of copper-plated carbon nanotubes, 0.13g / L of modified silica, and the rest is deionized water;
[0096] Step 3: Preparation of copper-plated carbon nanotubes:
[0097] Using deionized water as solvent, take 15 g / L of copper sulfate pentahydrate, 10.5 g of potassium sodium tartrate, and 20 g / L of ethylenediaminetetraacetic acid, stir evenly, add 2 mL / L of polyethylene glycol, then dropwise add sodium hydroxide solution, adjust the pH value to 11.5, and obtain plating solution A;
[0098] Take 0.1g carbon nanotubes and 50mL deionized water, and ultrasonically disperse them to obtain a carbon nanotube suspension. Add the carbon nanotubes to plating solution A, heat it to 68°C, add 4.5g / L formaldehyde, and electroplate for 115min to obtain copper-plated carbon nanotubes.
[0099] Step 4: Preparation of amino silicon dioxide:
[0100] Take 5g of silica and 300mL of anhydrous toluene, stir evenly, ultrasonically disperse for 25min, add 20g of aminopropyltriethoxysilane, heat to boiling after nitrogen filling, reflux at a constant temperature of 105°C for 47h, wash and dry to obtain amino silica;
[0101] Step 5: Preparation of modified silica:
[0102] Take 6 g of amino silica and 300 mL of deionized water, stir evenly, ultrasonically disperse for 25 min, heat to 57 ° C, add 1 g of 1H, 1H, 2H, 2H-perfluorooctyltriethoxysilane and 0.5 g of acetic acid, heat to 78 ° C, stir for 6.5 h, filter and dry to obtain modified silica.
[0103] Comparative Example 3: No amination treatment was performed on the silicon dioxide, and the rest was the same as in Example 1:
[0104] A preparation process of a high-strength alloy for antennas comprises the following steps:
[0105] Step 1: Preparation of aluminum alloy:
[0106] Mg, Si, Fe, Cu, Cr, Mn, Ti, Zn and Al are melted at 750°C, refined at 742°C for 50 min, left to stand for 35 min, cast, heat treated, then rough rolled, cold rolled, cleaned, annealed, cooled and polished to obtain an aluminum alloy;
[0107] The aluminum alloy includes the following components, in terms of weight percentage: 1.2wt% Mg, 0.8wt% Si, 0.3wt% Fe, 0.12wt% Cu, 0.08wt% Cr, 0.1wt% Mn, 0.05wt% Ti, 0.04wt% Zn, and the balance is Al;
[0108] Step 2: Take the aluminum alloy, pickle, wash with water, dry, and then place it in an electroplating solution for electroplating. The plating solution temperature is 60° C. and the electroplating time is 13 minutes; a high-strength alloy for antenna is obtained;
[0109] The composition of the electroplating solution is: 320 mL / L of copper sulfate, 90 mL / L of accelerator sodium citrate, 3 mL / L of polyethylene glycol, 0.2 g / L of carbon nanotube-silicon dioxide composite, and the rest is deionized water;
[0110] Step 3: Preparation of copper-plated carbon nanotubes:
[0111] Using deionized water as solvent, take 15 g / L of copper sulfate pentahydrate, 10.5 g of potassium sodium tartrate, and 20 g / L of ethylenediaminetetraacetic acid, stir evenly, add 2 mL / L of polyethylene glycol, then dropwise add sodium hydroxide solution, adjust the pH value to 11.5, and obtain plating solution A;
[0112] Take 0.1g carbon nanotubes and 50mL deionized water, and ultrasonically disperse them to obtain a carbon nanotube suspension. Add the carbon nanotubes to plating solution A, heat it to 68°C, add 4.5g / L formaldehyde, and electroplate for 115min to obtain copper-plated carbon nanotubes.
[0113] Step 4: Preparation of modified silica:
[0114] Take 6 g of silica and 300 mL of deionized water, stir evenly, disperse by ultrasonication for 25 min, heat to 57 ° C, add 1 g of 1H, 1H, 2H, 2H-perfluorooctyltriethoxysilane and 0.5 g of acetic acid, heat to 78 ° C, stir for 6.5 h, filter and dry to obtain modified silica;
[0115] Step 5: Preparation of carbon nanotube-silicon dioxide composite:
[0116] S1: Take 1000 mL of deionized water, add tris(hydroxymethylaminomethane) hydrochloric acid solution, adjust the pH value to 8.4, add 0.1 g of copper-plated carbon nanotubes and 3 g of dopamine hydrochloride powder, stir for 5 h, centrifuge and dry to obtain copper-plated carbon nanotubes coated with polydopamine;
[0117] S2: Take 100 mL of deionized water and 50 mL of anhydrous ethanol, stir evenly, add 1 g of copper-plated carbon nanotubes coated with polydopamine and 2 g of modified silica, heat to 68°C, ultrasonically disperse for 35 minutes, then stir for 5.5 hours, filter and dry to obtain a carbon nanotube-silica composite.
[0118] experiment:
[0119] The high-strength alloy for antenna with a thickness of 2 mm prepared in Examples 1 to 3 and Comparative Examples 1 to 3 was used for performance testing. The yield strength and tensile strength of the alloy were tested according to GB / T3880.2-2024; the friction and wear resistance of the alloy coating was tested using a friction and wear testing machine; the data obtained are as follows:
[0120] <![CDATA[Yield strength / MP a > <![CDATA[Tensile strength / MP a > Friction coefficient Example 1 137 235 0.22 Example 2 135 234 0.23 Example 3 138 236 0.22 Comparative Example 1 132 231 0.27 Comparative Example 2 121 220 0.25 Comparative Example 3 129 228 0.23
[0121] Conclusion: From the comparison of the data in the table, it can be seen that in Example 1, copper is not plated on the surface of the carbon nanotubes, the bonding force between the carbon nanotubes and the copper coating is deteriorated, the adhesion of the coating is reduced, the friction coefficient is increased, the friction and wear resistance of the alloy coating is deteriorated, and the strength of the alloy is deteriorated. In Example 2, the copper-plated carbon nanotubes are not compounded with modified silica, and the carbon nanotubes are easily agglomerated, thereby affecting the mechanical properties of the alloy for the antenna. In Example 3, silica is not subjected to amination treatment, the interface compatibility between amination silica and carbon nanotubes is poor, and the strength of the alloy for the antenna is reduced. In Examples 1 to 3 of the present invention, carbon nanotube-silicon dioxide composites are added to the electroplating solution to enhance the strength of the alloy for the antenna. The strength of the carbon nanotubes is high, and copper plating on the surface of the carbon nanotubes improves the conductivity of the antenna. At the same time, copper plating on the surface of the carbon nanotubes can improve the bonding force between the carbon nanotubes and the copper coating, and improve the adhesion of the electroplating layer, thereby enhancing the durability and reliability of the alloy for the antenna. The carbon nanotubes are compounded with modified silica to improve the agglomeration of the carbon nanotubes. The silica is first subjected to an amino treatment. The amino group can enhance the interaction between the amino silica and the carbon nanotubes, improve the interface compatibility between the two, and further enhance the strength of the alloy for the antenna.
[0122] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
Claims
1. A process for preparing a high-strength alloy for antenna, characterized in that: The following steps are involved: Step 1: Take Mg, Si, Fe, Cu, Cr, Mn, Ti, Zn, and Al, melt at 745-760°C, refine at 740-745°C for 40-60min, stand for 30-40min, cast, heat treat, and then perform rough rolling, cold rolling, cleaning, annealing, cooling, and grinding to obtain aluminum alloy; Step 2: Take the aluminum alloy, pickle it, wash it with water, dry it, and then place it in an electroplating solution for electroplating to obtain a high-strength alloy for antennas; The electroplating solution comprises: 300-350 mL / L of copper sulfate, 85-100 mL / L of an accelerator, 2-4 mL / L of polyethylene glycol, 0.1-0.3 g / L of a carbon nanotube-silicon dioxide compound, and the rest is deionized water.
2. The preparation process of a high-strength alloy for antenna according to claim 1, characterized in that: The aluminum alloy includes the following components, in weight percentage: 1wt%-1.5wt% Mg, 0.6wt%-0.9wt% Si, 0.1wt%-0.4wt% Fe, 0.1wt%-0.15wt% Cu, 0.07wt%-0.1wt% Cr, 0.05wt%-0.15wt% Mn, 0.04wt%-0.085wt% Ti, 0.03wt%-0.08wt% Zn, and the balance is Al.
3. The preparation process of a high-strength alloy for antenna according to claim 1, characterized in that: The preparation method of the carbon nanotube-silicon dioxide composite is as follows: The following steps are involved: S1: Take deionized water, add tris(hydroxymethylaminomethane) hydrochloric acid solution, adjust the pH value to 8.3-8.5, add copper-plated carbon nanotubes and dopamine hydrochloride powder, stir for 5-6 hours, centrifuge and dry to obtain copper-plated carbon nanotubes coated with polydopamine; S2: Take deionized water and anhydrous ethanol, stir evenly, add copper-plated carbon nanotubes coated with polydopamine and modified silica, heat to 65-70°C, ultrasonically disperse for 30-40 minutes, then stir for 5-6 hours, filter and dry to obtain a carbon nanotube-silica composite.
4. The process for preparing a high-strength alloy for antenna according to claim 3, characterized in that: The preparation method of the copper-plated carbon nanotubes is as follows: carbon nanotubes and deionized water are ultrasonically dispersed to obtain a carbon nanotube suspension, the carbon nanotubes are added to a plating solution A, the temperature is raised to 65-70° C., formaldehyde is added, and electroplating is performed for 110-120 minutes to obtain copper-plated carbon nanotubes.
5. The process for preparing a high-strength alloy for antenna according to claim 4, characterized in that: The preparation method of the plating solution A is as follows: using deionized water as a solvent, taking copper sulfate pentahydrate, potassium sodium tartrate, and ethylenediaminetetraacetic acid, stirring evenly, adding polyethylene glycol, and then dropping a sodium hydroxide solution, adjusting the pH value to 11-12, and obtaining the plating solution A.
6. The process for preparing a high-strength alloy for antenna according to claim 3, characterized in that: The preparation method of the modified silicon dioxide is as follows: taking amino silicon dioxide and deionized water, stirring evenly, ultrasonically dispersing for 20-30 minutes, heating to 55-60° C., adding 1H,1H,2H,2H-perfluorooctyltriethoxysilane and acetic acid, heating to 75-80° C., stirring for 6-7 hours, filtering and drying to obtain the modified silicon dioxide.
7. The process for preparing a high-strength alloy for antenna according to claim 6, characterized in that: The preparation method of the amino silicon dioxide is as follows: taking silicon dioxide and anhydrous toluene, stirring evenly, ultrasonically dispersing for 20-30 minutes, adding aminopropyltriethoxysilane, heating to boiling after nitrogen filling, reflux at a constant temperature of 105° C. for 46-50 hours, washing and drying to obtain the amino silicon dioxide.
8. The process for preparing a high-strength alloy for antenna according to claim 1, characterized in that: The accelerator is any one or more of sodium citrate and potassium tartrate.
9. The process for preparing a high-strength alloy for antenna according to claim 1, characterized in that: In step 2, during the electroplating process, the plating solution temperature is 55-65° C. and the electroplating time is 12-15 minutes.
10. A high-strength alloy for antenna prepared according to the preparation process of a high-strength alloy for antenna according to any one of claims 1 to 9.
Citation Information
Patent Citations
Method for preparing inorganic particle / epoxy resin super hydrophobic film
CN102702553A
6061 alloy and preparation process thereof
CN104357719A
Method for preparing boron phosphate coated carbon nanotube composite proton exchange membrane
CN105390721A
Preparation process of acid-corrosion-resistant functional ceramic membrane for aluminium-alloy surface
CN109402699A
Aluminium alloy material, conductive member using same, battery member, fastening component, spring component, and structure component
CN110475885A